Regressão binária nas abordagens clássica e bayesiana - Fernandes, Amélia Milene Correia (2016)
The objective of this work is to study the binary regression model under the frequentist and Bayesian approaches using the probit, logit, log-log complement, Box-Cox transformation and skewprobit as link functions. In the classical approach we presented assumpti- ons and procedures used in the regression modeling. We verified the accuracy of the estimated parameters by building confidence intervals and conducting hypothesis tests. In the Bayesian appro- ach we made a comparative study using two methodologies. For the first methodology, we considered non-informative prior dis- tributions and the Metropolis-Hastings algorithm to estimate the model. In the second methodology we used auxiliary variables to obtain the known a posteriori distribution, allowing the use of the Gibbs Sampler algorithm. However, the introduction of these auxiliary variables can generate correlated values and needs the use of clustering of unknown quantities in blocks to reduce the autocorrelation. In the simulation study we used the AIC and BIC information criteria to select the most appropriate model and we evaluated whether the coverage probabilities of the confidence interval is in agre- ement with that expected by the asymptotic theory. In Bayesian approach we found that the inclusion of auxiliary variables in the model results in a more efficient algoritm according to the MSE, MAPE and SMAPE criteria. In this work we also present applications to two real datasets. The first dataset used is the variation of the Ibovespa and variation of the daily value of the American dollar at the time of closing the 2013 to 2016. The second dataset, used is an educational data set (INEP-2013), where we are interested in studying the factors that infuence the approval of the student.